2022
DOI: 10.1007/s00253-022-11815-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity in different outdoor pilot plant photobioreactor types during production of the microalga Nannochloropsis sp. CCAP211/78

Abstract: As large-scale outdoor production cannot be done in complete containment, cultures are (more) open for bacteria, which may affect the productivity and stability of the algae production process. We investigated the bacterial diversity in two indoor reactors and four pilot-scale outdoor reactors for the production of Nannochloropsis sp. CCAP211/78 spanning four months of operation from July to October. Illumina sequencing of 16S rRNA gene amplicons demonstrated that a wide variety of bacteria were present in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…In their study, they used P. tricornutum strain CCAP 1052/1B, which is a deposition of strain U640, and interestingly the bacterial community composition was very different to the ones observed in our study. In a study of Lian et al (2022) the bacterial community composition in different pilot-scale photobioreactors producing Nannochloropsis sp. was shown to correlate significantly with the nitrate concentration, and Tait et al (2019) observed a shift in the bacterial community composition associated with a freshwater Chlorella sp .…”
Section: Discussionmentioning
confidence: 99%
“…In their study, they used P. tricornutum strain CCAP 1052/1B, which is a deposition of strain U640, and interestingly the bacterial community composition was very different to the ones observed in our study. In a study of Lian et al (2022) the bacterial community composition in different pilot-scale photobioreactors producing Nannochloropsis sp. was shown to correlate significantly with the nitrate concentration, and Tait et al (2019) observed a shift in the bacterial community composition associated with a freshwater Chlorella sp .…”
Section: Discussionmentioning
confidence: 99%
“…Saprospirales can indeed be found in various environments, such as saline water, freshwater, soil, bioreactors, and wastewater treatment plants, as has been already mentioned in various studies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In addition, air, plants, as well as terrestrial and saline water hosts are also potential environments for Saprospirales.…”
Section: Discussionmentioning
confidence: 80%
“…In the last two decades, numerous studies have reported the presence of bacteria belonging to the order of Saprospirales in various artificial and natural ecosystems. Bacteria belonging to Saprospirales can be found in natural ecosystems such as marine and freshwater environments, and soils [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Furthermore, several studies have reported that Saprospirales members can be found in wastewater treatment plants, and especially in activated sludge and anaerobic ammonium oxidation reactors [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nitrate concentration, for instance, was suggested to be a primary driver in the bacterial community composition of outdoor Nannochloropsis sp. cultures [18]. Finally, several studies indicated that nutrient depletion may also increase the algal production of extracellular polymeric substances (EPS), another possible fermentation substrate.…”
Section: The Impact Of Nutritional Status At Harvestmentioning
confidence: 99%